(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Determining the rate of malnutrition and related factors of patients with chronic renal failure undergoing peritoneal dialysis at Thong Nhat Hospital in Ho Chi Minh City in 2020. Subject and method: A cross-sectional study was conducted in 49 patients with chronic kidney failure undergoing peritoneal dialysis at Thong Nhat Hospital in Ho Chi Minh City, data were collected using available questionnaires and anthropometric measurements. Results: The prevalence of malnutrition according to SGA was 44.9%, of which 16.3% have severe malnutrition (SGA-C) and 28.6% moderate malnutrition (SGA-B). The proportion had significantly gender (p=0.041), diabetes mellitus (p=0.008), malnutrition of BMI (p=0.007), decreased arm circumference (p<0.001), decreased muscle strength (p=0.031) and decreased blood albumin (p=0.001). Conclusion: The rate of malnutrition in patients with chronic renal failure on peritoneal dialysis was quite high. It is necessary to have a comprehensive Nutrition assessment and intervention strategy for the above subjects.